The Role of Teachers in Implementing Independent Curriculum Based Learning - Herlina; Agus Pahrudin; Agus Jatmiko; Koderi (CV. Creative Tugu Pena, 2024)
Education plays a major role in improving the quality of human resources (Human Receources). One of the latest innovations in education in Indonesia is the Independent Curriculum launched in 2022, which emphasizes active student participation in learning to increase creativity and innovation. In its implementation, teachers play a crucial role as the main implementers of the curriculum. This article discusses the role of teachers in implementing the Independent Curriculum, starting from learning planning, adapting teaching methods, to evaluation. This study uses a descriptive qualitative method through a literature review, namely from written sources, both printed and electronic. The results show that the success of implementing the curriculum is highly dependent on the ability of teachers to overcome existing challenges, such as limited facilities, professional readiness, and adjustments to teaching methods. With the right strategy, the role of teachers in implementing the Independent Curriculum can support the progress of education in Indonesia.